Contemporary labor economics - McConnell, Campbell R.; Brue, Stanley L. 1945-; Macpherson, David A. 1960- (McGraw-Hill Education, 2021)
One benefit of authoring a text that has met the test of the market is the opportunity to revise. Revision provides for improvement to delete the archaic and install the novel, to rectify errors of omission or commission, to rewrite misleading or obscure statements, to introduce more relevant illustrations, to bring more recent data to bear, to upgrade organizational structure, and to enhance pedagogical aids in short, to build on an accepted framework of ideas. We feel that those who examine this new twelfth edition of Contemporary Labor Economics will agree that we have fully exploited this opportunity--Provided by publisher.